2018
DOI: 10.3171/2017.4.jns17557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on outcome after aneurysmal subarachnoid hemorrhage treated with clipping versus coiling

Abstract: OBJECTIVE It has been suggested that increased body mass index (BMI) may confer a protective effect on patients who suffer from aneurysmal subarachnoid hemorrhage (aSAH). Whether the modality of aneurysm occlusion influences the effect of BMI on patient outcomes is not well understood. The authors aimed to compare the effect of BMI on outcomes for patients with aSAH treated with surgical clipping versus endovascular coiling. METHODS The authors retrospectively reviewed the outcomes for patients admitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…There would be some potential biases and known and unknown confounders in this study. The patients with WFNS 4‐5 (23.1%) and mFS 3‐4 (63.3%) were consistent with other studies (WFNS: 22.4%‐31.1%; mFS: 56.2%‐77.7%). Additionally, all CT grades were evaluated by two blinded senior neurologists.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There would be some potential biases and known and unknown confounders in this study. The patients with WFNS 4‐5 (23.1%) and mFS 3‐4 (63.3%) were consistent with other studies (WFNS: 22.4%‐31.1%; mFS: 56.2%‐77.7%). Additionally, all CT grades were evaluated by two blinded senior neurologists.…”
Section: Discussionsupporting
confidence: 91%
“…12 Although VG was developed by two early predictors, and available for risk stratification at the time after SAH, the AUC was not large according to results from recent study. 15 mFS: 56.2%-77.7% 20,26,36 ). Additionally, all CT grades were evaluated by two blinded senior neurologists.…”
Section: Discussionmentioning
confidence: 99%
“…For example, protective mechanisms might relate to an increased metabolic reserve of adipose or muscle mass, which could improve tolerance of major catabolic and inflammatory events among critically ill patients treated in ICUs. Supporting this theory, a few studies [3,8,34] have related obesity to more favorable outcomes, measured using the modified Rankin Scale (mRS), and milder overweight to lower complication rates as well. On the other hand, other studies have reported contradictory findings [33,37,44].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other factors, such as SAH severity and rebleeding, have been associated with higher mortality rates; no evidence relates these findings to obesity groups. Furthermore, Rinaldo et al [34] found an effect of BMI on SAH outcome, and this effect varied depending on the treatment modality (clipping versus coiling). However, the study found no differences after using the validated WHO categories for BMI.…”
Section: Confounders In Studies On the Obesity Paradox In Sahmentioning
confidence: 99%
“…Furthermore, according to the literature, there is a direct positive relation to the body mass index, which we did not assess. Rinaldo et al (2018) determined that patients with a body mass index of greater than 32.3kg/m 2 (as well as metabolic syndrome) had a lower frequency of poor functional outcome after 90 days or more.…”
Section: Discussionmentioning
confidence: 99%